2016
DOI: 10.4269/ajtmh.16-0410
|View full text |Cite
|
Sign up to set email alerts
|

High Efficacy of Primaquine Treatment for Plasmodium vivax in Western Thailand

Abstract: Abstract. Primaquine is the only licensed antimalarial drug that is capable of clearing dormant Plasmodium vivax liver stage parasites. To date, there is no clear evidence of resistance of the liver stage parasite against this drug, because of the difficulty in ascertaining the cause of recurrent infection. We followed 52 Thai P. vivax patients for 9 months after directly observed treatment of 15 mg primaquine daily for 14 days. Blood samples taken at 2-4 weekly intervals were assessed by microscopy and polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…This study investigated the frequencies of sequence variations in eleven drug-metabolizing enzymes contributing to phase I (CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5) and Phase II (COMT, SULT1A1, SULT1A4 and UGT2B7) metabolism of PQ and CQ as well as seven drug transporter genes (ABCB1, ABCA1, ABCC2, ABCC4, ABCG2, SLCO1B1 and SLC25A40) in 51 Thai patients infected with P. vivax. Although the influence of drug-metabolizing enzymes and drug transporters on the efficacy of PQ treatment on P. vivax infection has been studied, 7,14,16,27 their contribution to relapse is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study investigated the frequencies of sequence variations in eleven drug-metabolizing enzymes contributing to phase I (CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5) and Phase II (COMT, SULT1A1, SULT1A4 and UGT2B7) metabolism of PQ and CQ as well as seven drug transporter genes (ABCB1, ABCA1, ABCC2, ABCC4, ABCG2, SLCO1B1 and SLC25A40) in 51 Thai patients infected with P. vivax. Although the influence of drug-metabolizing enzymes and drug transporters on the efficacy of PQ treatment on P. vivax infection has been studied, 7,14,16,27 their contribution to relapse is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CYP2D6 metabolizer status influences PQ efficacy. 7,14 Bennette et al 7 first described that two study participants (6%), one PM with a CYP2D6*5/*6 genotype and one IM with a CYP2D6*4/*41 genotype signifying considerable decreased activity, had multiple relapses of P. vivax while participants with genotypes predicting normal metabolizer (NM) status were not found to relapse. Furthermore, relapse patients had significantly higher amounts of the parent drug PQ AUC inf (p<0.001) compared with non-relapse patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal study in Thailand was conducted from April 2014 to September 2015, as described [ 21 ]. Briefly, 57 symptomatic P .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the latent phase of hypnozoites in the liver often found in Plasmodium ovale and Plasmodium vivax infection can cause relapses in about 50-80% of malaria sufferers (Chu and White, 2016). Primaquine (PQ), recognized as the primary treatment for the hepatic phase of malaria (Longley et al, 2016), is an antimalarial pro-drug compound belonging to the 8-aminoquinoline group that actively works against sporozoites, hypnozoites, asexual phases and gametocytes through inhibition of the metabolic activity of mitochondrial parasites and the production of reactive metabolites, which are toxic to cells (Chu and White, 2016;Marcsisin et al, 2016). PQ constitutes a drug with a short half-life, which is rapidly metabolized by the liver into a carboxylic acid derivative ultimately excreted in the urine.…”
mentioning
confidence: 99%